Rwanda : 2012 Article IV Consultation and Fifth Review under the Policy Support Instrument and Request for Modification of Assessment Criteria -Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2013)
The article summarizes the positive economic development of Rwanda and its internal and external policies. Rwanda's economy is referred to as a success story, but it also faces certain challenges. The country is focused on maintaining macroeconomic stability, sustaining sturdy growth, and reducing poverty without foreign dependence. Fiscal and monetary policies have played key roles in economic growth. External stability is manageable, as it has significant profit in the global market. The authorities review this remarkable success of Rwanda's economy as a great achievement.